Pelatihan Pengenalan Psikologis Konsumen pada Pelaku UMKM Binaan Rumah BUMN Sumbawa - Yeldy Dwi Genadi; Sherwin Ary Busman; Abdurrahman; Adrianda Anwar; Zamroni Alpian Muhtarom (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
MSMEs (Micro, Small and Medium Enterprises) play an important role in the local and national economy. However, they often face challenges in understanding consumer behavior and preferences that can affect the success of their business. This training aims to introduce consumer psychology to MSME players assisted by Rumah BUMN in Sumbawa. The training involved 40 MSME players who participated in the Rumah BUMN-assisted program. Through practical approaches and case studies, this training will help participants to apply consumer psychological knowledge in their marketing strategies and product development. The main objective is to improve their understanding of consumer needs, expectations and preferences and to help them identify new business opportunities. It is expected that this training will provide long-term benefits for MSME players in improving the quality of their products and services, expanding market share, and building stronger relationships with consumers. In addition, the training can also contribute to local economic growth through improved MSME performance and increased competitiveness in the market, resulting in increased sales volume.